2009
DOI: 10.1359/jbmr.081254
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Treatment Reduces Undercarboxylated Osteocalcin but Does Not Alter Bone Turnover, Density, or Geometry in Healthy Postmenopausal North American Women

Abstract: Low vitamin K status is associated with low BMD and increased fracture risk. Additionally, a specific menaquinone, menatetrenone (MK4), may reduce fracture risk. However, whether vitamin K plays a role in the skeletal health of North American women remains unclear. Moreover, various K vitamers (e.g., phylloquinone and MK4) may have differing skeletal effects. The objective of this study was to evaluate the impact of phylloquinone or MK4 treatment on markers of skeletal turnover and BMD in nonosteoporotic, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 48 publications
10
80
2
3
Order By: Relevance
“…Several protein targets of vitamin K are osteoblastic proteins and components of the bone matrix including osteocalcin, matrix Gla protein, protein S, and Gas 6 (27,28). Under-carboxylated osteocalcin has been reported to correlate with BMD and hip fracture risk in elderly women (29,30), while vitamin K treatment effectively reduces under-carboxylated osteocalcin (31). The association between vitamin K levels and the osteocalcin carboxylation state has led to the suggestion that the primary mechanism underlying the protective influence of vitamin K on bone may involve carboxylation of osteocalcin (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protein targets of vitamin K are osteoblastic proteins and components of the bone matrix including osteocalcin, matrix Gla protein, protein S, and Gas 6 (27,28). Under-carboxylated osteocalcin has been reported to correlate with BMD and hip fracture risk in elderly women (29,30), while vitamin K treatment effectively reduces under-carboxylated osteocalcin (31). The association between vitamin K levels and the osteocalcin carboxylation state has led to the suggestion that the primary mechanism underlying the protective influence of vitamin K on bone may involve carboxylation of osteocalcin (26).…”
Section: Introductionmentioning
confidence: 99%
“…The association between vitamin K levels and the osteocalcin carboxylation state has led to the suggestion that the primary mechanism underlying the protective influence of vitamin K on bone may involve carboxylation of osteocalcin (26). However, recent clinical data contrast with this notion and suggest that vitamin K treatment at doses capable of correcting under-carboxylated osteocalcin in healthy postmenopausal women do not correlate with altered bone turnover, density, or geometry (31). Consequently, a direct cause-effect relationship between osteocalcin Á-carboxylation and effects of vitamin K on bone mass remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Phylloquinone can also increase cOC in older adults 77 and lower ucOC/OC 78 but results for younger adults are inconclusive 77,79 . Furthermore, 45mg/d MK4 significantly decreased ucOC in postmenopausal women 71,72,76,80,81 , increased cOC and generally increased total OC 80,81 , although 1.5mg/d may be sufficient to decrease serum ucOC and ucOC/OC while increasing cOC 82 ; a dose of 1.5mg/d accords with the amount of MK4 obtainable from diet, whereas 45mg/d is pharmacological 83 .…”
Section: Bonementioning
confidence: 95%
“…In addition, a 2009 review and subsequent study showed that phylloquinone can dose-dependently reduce ucOC in postmenopausal women, with a consistently effective dose being 1mg/d, although there were inconsistent results for total OC 69,76 . Phylloquinone can also increase cOC in older adults 77 and lower ucOC/OC 78 but results for younger adults are inconclusive 77,79 .…”
Section: Bonementioning
confidence: 99%
“…Published commentary have also questioned the findings. (1,19,(26)(27)(28) Results of several placebo-controlled clinical trials of vitamin K 1 are now being reported. One (29) showed a modest positive effect of 200 mg/d of K 1 for 2 yr on BMD at the distal radius but not at any other skeletal site.…”
mentioning
confidence: 99%